The Effectiveness of Interactive Learning Media Using SAC (Smart Apps Creator) Software to Improve Understanding of Physics Concepts and Pancasila Student Profiles - Safitri, Catur Windi; Maftukhin, Arif; Akhdinirwanto, Raden Wakhid (CV. Rayyan Dwi Bharata, 2025)
The aim of this interactive media development research is to determine its feasibility in terms of validity, practicality and effectiveness in increasing understanding of physics concepts and the profile of Pancasila students. The ADDIE research method, which stands for Analysis, Design, Development, Implementation and Evaluation, was used in this research. The research subjects used were a narrow trial on 12 students and a wide trial on 36 students carried out at SMA Negeri 6 Purworejo. The tools used are validation sheets, physics concept understanding test sheets, student reaction questionnaires to the media, independent Pancasila student profile questionnaire sheets, and learning implementation sheets. The research results show: 1) The validity of interactive teaching materials created with SAC (Smart Apps Creator) software. 2) The average value of the application of science through the media is 97.95%, included in the very good category. 3. Evaluation of the survey results of student responses to print media produced an average score of 87.4% in the very good category. The Pancasila student profile questionnaire which was answered independently via pretest-posttest produced an N-gain of 0.7 in the medium category. and the results of this research show the effectiveness of interactive learning media using SAC (Smart Apps Creator) software. Creating interactive learning materials using Pancasila student profiles and SAC (Smart Apps Creator) software to improve understanding of physics concepts has proven to be practical, efficient and practicable.